Pengembangan Karakter Anak melalui Kurikulum Tematik Terpadu di Sekolah Dasar - Nurhaliza, Siti; Fauzan, Ahmad; Husna, Lailatul (FONDASI: Jurnal Pendidikan Dasar, 2026)
Character development is a central goal of primary education that must be implemented in a systematic and sustainable manner. An integrated thematic curriculum is considered a relevant approach because it enables the integration of character values across all subjects and learning activities. This study aims to describe and analyze children’s character development through the implementation of an integrated thematic curriculum in primary schools. The study adopts a qualitative approach with a descriptive design. Data were collected through classroom observations, in-depth interviews with teachers and school principals, and analysis of instructional documents. Data analysis was conducted through data reduction, data display, and continuous conclusion drawing.The results show that the integrated thematic curriculum effectively develops children’s character in an integrated and contextual way. The character values that emerged include honesty, responsibility, discipline, hard work, social care, mutual cooperation, nationalism, and integrity. These values are internalized through theme-based lesson planning, the use of active learning methods, teacher role modeling, and consistent habituation during learning activities. Teachers play a key role as facilitators and character models, while the school environment functions as a space for reinforcing values. The study also identifies challenges, including limited instructional time, differences in student characteristics, and variations in teachers’ competence in integrating character values. This study concludes that an integrated thematic curriculum is an effective means of developing children’s character in primary schools when supported by careful planning, teacher competence, and collaboration among all members of the school community.